2005
DOI: 10.1111/j.1525-139x.2005.18204.x
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Diagnostic and Interventional Nephrology Section Editor: Stephen Ash: Does Catheter Insertion by Nephrologists Improve Peritoneal Dialysis Utilization? A Multicenter Analysis

Abstract: In contrast to hemodialysis (HD), peritoneal dialysis (PD) remains an underutilized form of renal replacement therapy in the United States. Although a variety of factors have been deemed responsible, timely insertion of a PD catheter may also be a contributory factor. We conducted a multicenter analysis to examine whether the establishment of a program for PD catheter insertion by nephrologists has a positive impact on the growth in the number of patients using PD. Data for catheter insertion performed by neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…The inclusion of interventional nephrologist catheter placement in the integrated care approach to dialysis start has resulted in a relatively large PD penetration of 44.8% in one of the reports [ 32 ]. Another study reported an increase in the prevalence of PD from the relative share of 16–18% to 22–32% [ 33 ]. Catheter implantation by nephrologists compared to surgical or radiological services was associated with higher rates of successfully finalised peritoneal dialysis utilisation in patients undergoing elective PD catheter insertion [ 34 ].…”
Section: Peritoneal Catheter Insertion By Nephrologistsmentioning
confidence: 99%
“…The inclusion of interventional nephrologist catheter placement in the integrated care approach to dialysis start has resulted in a relatively large PD penetration of 44.8% in one of the reports [ 32 ]. Another study reported an increase in the prevalence of PD from the relative share of 16–18% to 22–32% [ 33 ]. Catheter implantation by nephrologists compared to surgical or radiological services was associated with higher rates of successfully finalised peritoneal dialysis utilisation in patients undergoing elective PD catheter insertion [ 34 ].…”
Section: Peritoneal Catheter Insertion By Nephrologistsmentioning
confidence: 99%
“… 1 2 3 4 The availability of timely PD catheter insertion, low rate of complication related with procedure and the low rate of catheter failure with effort of nephrologists are important requisites that will increase the utility of PD and reduce patient morbidity. 1 5 6 The blind percutaneous PD catheter insertion by nephrologists shows similar outcome to catheter insertion performed by surgeons, and it is advantageous in that it can timely initiate dialysis therapy and does not require an operating room. 5 6 7 8 9 10 11 12…”
Section: Introductionmentioning
confidence: 96%
“… 1 5 6 The blind percutaneous PD catheter insertion by nephrologists shows similar outcome to catheter insertion performed by surgeons, and it is advantageous in that it can timely initiate dialysis therapy and does not require an operating room. 5 6 7 8 9 10 11 12…”
Section: Introductionmentioning
confidence: 96%
“…In fact, the success of PD access procedures performed by nephrologists using various techniques has been well documented [812]. Catheter insertion by nephrologists has been shown to improve PD utilization and increase the PD population growth rate in other parts of the world [9, 11, 13, 14]. …”
mentioning
confidence: 99%
“…Although peritoneoscopic implantation of PDC provides direct visualization, the introduction of the peritoneoscope still involves blind insertion through the abdominal wall. Therefore, bowel perforation remains a potential serious complication [13]. Pneumoperitoneum and pneumomediastinum are the rare complications caused by the air insufflation.…”
mentioning
confidence: 99%